Effect of Tocotrienols on Aortic Adventitia of Cholesterol-Fed Rabbits - Uzma Shahid, Asma Hafeez, Kaukab Anjum, Zubia Athar, Nomana Mahmood (Journal of Islamic International Medical College, 2017)
Objective: To identify the effect of tcotrienols on adventitial changes induced by high cholesterol diet in descending thoracic aorta of rabbits. Study Design: Laboratory based randomized control trial. Place and Duration of Study: The Anatomy department of Army Medical College Rawalpindi in collaboration with National Institute of Health, Islamabad. The study commenced on 10 March 2009 and completed on 10 September 2009. Materials and Methods: Thirty adult male New Zealand White rabbits were randomly divided into three equal groups (I, II & III). Group-I consumed standard NIH diet while group-II was fed 2% high cholesterol diet. Group-III animals were given the same diet as to group II, however, tocotrienols 6 mg/kg body wt/day were also added to the diet. Following six weeks of experiment, aorta of every animal was dissected. Cross sections were taken from descending thoracic aorta and processed for light microscopic examination. In H&E and verhoeff stained slides, adventitial histomorphological changes were compared among the three groups. Results: In rabbits on standard diet, tunica adventitia was a thin layer composed of loose network of collagen and elastic fibers which lacked lamellar pattern as that of media. Adventitial cells were relatively scanty. In contrast, aortic adventitia in group-II was thickened with increased number of inflammatory cells characterized by central round nucleus and foamy cytoplasm. Above mentioned histological changes were present in group- III but were of lesser degree than group-II. Mean±SD thickness of adventitia and inflammatory cells score was significantly greater in group-II &III when either was compared with group-I. However, group-III showed 19% (p<0.05) reduction in adventitial thickening and & 36% (p<0.05) lesser inflammatory cells score versus group-II. Conclusion: Tocotrienols decrease adventitial thickening and inflammation induced by high cholesterol diet in aorta of cholesterol-fed rabbits.